First record of Cecilioides acicula (Müller, 1774) Ferussaciidae, from Buenos Aires Province, Argentina - Díaz, Ana Cristina (2017)
Cecilioides acicula (Müller, 1774), family Ferussadidae, is native to the Palaearctic region but has been dispersed around the word by human activity. Here, we report the presence of this introduced spedes in La Plata city, Buenos Aires province, Argentina. This snail is largely subterranean and frequently is found in old graves in association with skeletal remains. Our samples were collected from sediments from the Municipal Cemetery of La Plata, Buenos Aires province, Argentina.